(untitled) (LEARNing Landscapes, 2022)
“Tell me about your research.” How does one begin to convey the importance of our life’s work—our research? Enter stage right, Research-based Theatre, an innovative, arts-based methodology that takes research data and brings it to life, by showing, rather than telling. In this article, we tell the story of how Research-based Theatre first came to be, and why it is especially well suited to the contemporary challenge of showcasing diverse and marginalized voices. We also share a short scene that illustrates the methodology in practice. We conclude by offering ways Research-based Theatre can be a meaningful approach for pedagogy and community-engaged initiatives.